Critical Role of p38 in Spinal Cord Injury by Regulating Inflammation and Apoptosis in a Rat Model. Issue 7 (1st April 2020) - Zhang, Heng-Wei; Ding, Jian-Dong; Zhang, Zeng-Shan; Zhao, Si-shun; Duan, Kang-ying; Zhu, Bao-qi; Zhao, Wen-Feng; Chai, Zong-Tao; Liu, Xiao-Wei
Abstract : Study Design: To evaluate the effect of p38 pathway on spinal cord injury (SCI), a rat model of SCI was performed. Objective: We determined the effect of p38 on SCI and SCI related inflammation, apoptosis, and autophagy. Summary of Background Data: SCI is a severe clinical problem worldwide. It is difficult to prevent cell necroptosis and promote the survival of residual neurons after SCI. p38, a class of mitogen-activated protein kinases, its effect on SCI and SCI related inflammation, apoptosis, and autophagy have not been studied very well. Methods: The rats were randomly divided into the following four groups: the sham-operated (sham) group, the SCI group, the SCI + vehicle group, and the SCI + SB203580 (10 mg/kg) group. The p38 inhibitor SB203580 was administered by oral (10 mg/kg/d) gavage once per day for 14 days. Neurological recovery was assessed using the Basso, Beattie, and Bresnahan locomotion rating scale. Apoptosis, autophagy, and inflammation related proteins were measured by enzyme-linked immunosorbent assay kits or western blotting. Results: Our results showed that p38 was upregulated after SCI from day 3, which was paralleled with the levels of its proteins ATF-2, suggesting an increase in p38 activity. Our results showed administration of SB203580 attenuated histopathology and promoted locomotion recovery in rats after SCI. SB203580 administration significantly inhibited inflammatory cytokines levels as well as the inflammation signaling pathway. SB203580 administration also modulated the apoptosis and autophagy signaling pathway. Conclusion: Our findings suggest that p38 inhibitor SB203580 treatment alleviates secondary SCI by inhibiting inflammation and apoptosis, thereby promoting neurological and locomoter functional recovery, thus suggest the important role of p38 in neuronal protection after SCI. Level of Evidence: N/A Abstract : Spinal cord injury is a severe clinical problem worldwide, the effect of p38 on SCI has not been investigated well. In this study, we investigated that p38 inhibitor SB203580 treatment alleviates secondary SCI by inhibiting inflammation and apoptosis, suggested the important role of p38 in neuronal protection after SCI.